Analisa Hari Rawat Inap dan Frekuensi Foto Thorak Terhadap Rata-rata Dosis Serap Radiasi Pada Pasien Covid-19 di Ruang Isolasi RSU Karsa Husada Batu - Muhammad Erfansyah; Sentot Alibasah; Yuly Peristiowati (Poltekkes Kemenkes Semarang, 2022)
Background: In the treatment process of patients covid-19 thorak photo action is done periodically every three days, the average length of hospitalization of covid patients in the isolation room at least 9 days and or up to the results of negatip swab tests and normal thorak photo images. The purpose of the study was to analyze the effect of hospitalization days and the frequency of action on the amount of radiation absorption dose received by Covid-19 patients in Covid-19 isolation rooms, as an evaluation material to improve aspects of occupational safety and health in the environment and society (patients).Methods: Design observational research with a cross-sectional approach. The population of all Covid-19 patients in isolation rooms at RSU Karsa Husada is 200 people. A sample of 200 respondents with probability sampling techniques. Independent variables are the length of hospitalization and frequency of thoracic photos. The dependent variable is the average dose of radiation absorption in the patient.Results: The results showed no long-standing effect of hospitalization on the average dose of radiation absorption in patients (p-value 0.030) and there was a effect on the frequency of thorax photos against the average dose of radiation absorption in patients (p-value 0.000).Conclusions: This research can be developed using more specific variables and with a larger population as well as more variation.